2022
DOI: 10.34172/mejdd.2022.255
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Complications in an Iranian Teaching Hospital

Abstract: BACKGROUND: Colonoscopy is generally a safe procedure with a limited number of adverse events. Few studies have addressed the rate of adverse events in teaching hospitals. This study aimed to investigate the rate of complications after colonoscopy performed by gastroenterology fellows in a teaching hospital in Tehran. METHODS: A historical cohort study was carried out to link the colonoscopy reports and the hospital information system to identify serious adverse events leading to unplanned hospitalization, unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Although the rate of these complications is not high, particularly after following the already-issued colon cancer screening guidelines. 13 Additionally, open-access endoscopy units have led to an increase in inappropriate referrals in Western countries. 10,14 A previous study from Switzerland showed a significant proportion of inappropriate colonoscopies.…”
mentioning
confidence: 99%
“…Although the rate of these complications is not high, particularly after following the already-issued colon cancer screening guidelines. 13 Additionally, open-access endoscopy units have led to an increase in inappropriate referrals in Western countries. 10,14 A previous study from Switzerland showed a significant proportion of inappropriate colonoscopies.…”
mentioning
confidence: 99%